Mass transfer characteristics of nonaqueous phase liquid based on air-liquid interfacial area in variably saturated porous media - Anwar, Faisal (Springer Netherlands, 2013)
Vapor phase mass transfer is an important interphase transport process that dominates the overall transport phenomena in liquid-gas system in porous media. Volatilization of nonaqueous phase liquids (NAPLs) in porous media is such system that takes place during the remediation of volatile organic compound-contaminated soil using soil vapor extraction. Usually, interphase mass transfer coefficient is lumped together with the air-liquid interfacial area because of the inaccessibility to quantify this parameter due to the heterogeneous nature of the pore structure of the media and the morphology of the fluid distribution. In this paper, the air-liquid interfacial area is quantified using a simple method derived from pressure-saturation relationship in three glass bead media. A series of one-dimensional NAPL volatilization experiments were carried out in a horizontal column for the same porous media by using toluene as the single contaminant. Experiments were conducted for NAPL saturation range of 13.8 ~ 71 % and pore gas velocities of 0.1 ~ 2 cm/s, and lumped mass transfer coefficients were evaluated. Actual vapor phase mass transfer coefficients were calculated using corresponding air-liquid interfacial area for a specific NAPL saturation and characterized in dimensionless form for all porous media. Results revealed that the vapor phase mass transfer increases with pore gas velocities and grain sizes but decreases with NAPL saturation.